POLITICAL PHENOMENOLOGY OF LAW - ANTON PARLAGI (Challenges of the Knowledge Society)
The present paper is a presentation of three regulation phenomena that are characteristic of society: the phenomenon of antroponomic regulation, the phenomenon of socioeconomic regulation and the phenomenon of politonomic regulation. The paper is also a clear introduction to the most important concepts used in the field of political phenomenology of law.